2021
DOI: 10.1038/s41467-021-23216-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from oyster suggests an ancient role for Pdx in regulating insulin gene expression in animals

Abstract: Hox and ParaHox genes encode transcription factors with similar expression patterns in divergent animals. The Pdx (Xlox) homeobox gene, for example, is expressed in a sharp spatial domain in the endodermal cell layer of the gut in chordates, echinoderms, annelids and molluscs. The significance of comparable gene expression patterns is unclear because it is not known if downstream transcriptional targets are also conserved. Here, we report evidence indicating that a classic transcriptional target of Pdx1 in ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…We find a particularly strong match between the exocrine pancreatic-like cells of the pluteus larvae and a cluster of gut related cells in the flatworm that, similar to the pluteus, are located at the top of the gut ( 8 ). This finding further confirms the presence of pancreatic-like cells in protostomes and is only the second occurrence in ciliated larvae ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We find a particularly strong match between the exocrine pancreatic-like cells of the pluteus larvae and a cluster of gut related cells in the flatworm that, similar to the pluteus, are located at the top of the gut ( 8 ). This finding further confirms the presence of pancreatic-like cells in protostomes and is only the second occurrence in ciliated larvae ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
“…4). Exocrine pancreatic-like cells have been described in adults of cephalochordates, tunicates, cnidarians and in the pacific oyster ( 50, 51 ). Previously they have only been described in larval stages of the sea urchin S. purpuratus ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hepatopancreas is an organ with combined functions of the liver and pancreas ( Xu et al, 2021 ). The vertebrate hepatopancreas is also called the mid-intestinal gland ( Rőszer, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that site-specific genetic variants in the homeobox and HSP genes are essential regulators of body development and stress responses. As genetic divergence and its associated functional changes could strongly diversify the adaptive regulations and responses of oysters to environmental factors [28,[76][77][78], it is possible that the variance of environmental condition or source of oyster recruits between Shenzhen Bay and Lantau Island might lead to the possession of these genetic variants which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%